Bentuk-Bentuk Dominasi Laki-Laki Dalam Kumpulan Crita Cekak Janji Sejati Karya Kustri Sumiyardhana Menurut Kajian Feminisme - Sasanti, Ani; Zaidah, Nuning; Werdiningsih, Yuli Kurniati (Universitas PGRI Semarang, 2022)
This study aims to describe the forms of male domination in the collection of the crita cekak of the Janji Sejati by Kustri Sumiyardhana. The research method in this study is qualitative research. The source of the research data is a collection of crita cekak Janji Sejati by Kustri Sumiyardhana by choosing six cerkak. They are Nalika Srengenge Anglsup, Primbon, Janji Sejati, Pegatan, Dhukuhe Sumar and Nulung. The data are in the form of phrases, clauses, and sentences that contain elements of forms of male domination. The data collection technique used a document study with the stages of reading and taking notes. This study uses data analysis techniques in the form of data reduction, data display and data verification. The theoretical study chosen is the study of feminism with a focus on forms of male domination.The results obtained by this study found that there are forms of male domination in the collection of crita cekak Janji Sejati by Kustri Sumiyardhana, namely subordination or unimportance, stereotypes or negative labeling, violence including physical violence, psychological violence, sexual violence and economic violence. Forms of male domination occur in the family, community and public spheres